2014
DOI: 10.1111/bju.12767
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum cholesterol is an independent prognostic factor for patients with renal cell carcinoma (RCC)

Abstract: ObjectiveTo assess the prognostic role of preoperative serum cholesterol in patients with renal cell carcinoma (RCC), as increasing evidence suggests that alterations in the lipid profile are associated with the development, progression and prognosis of various cancers. Patients and MethodsWe analysed 867 patients, who underwent radical or partial nephrectomy for RCC between 2002 and 2012. Preoperative total cholesterol levels were determined in serum using colorimetric analysis (CHOD-PAP method). The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Previous study indicated that the infiltration of lymphocyte (CD4 + /CD8 + T‐lymphocytes) might affect patients’ response for neoadjuvant chemotherapy in urothelial carcinoma of the bladder, and our previous work also revealed that low preoperative neutrophil to lymphocyte ratio was independently associated with worse survival outcomes . In addition, low serum cholesterol levels was also associated with poor survival in colorectal cancer and renal cell carcinoma, but the specific mechanism remained to be elucidated. In all, CONUT, a combination of these three indictors above, is more powerful and can be applicated in current risk stratifications of UTUC.…”
Section: Discussionmentioning
confidence: 91%
“…Previous study indicated that the infiltration of lymphocyte (CD4 + /CD8 + T‐lymphocytes) might affect patients’ response for neoadjuvant chemotherapy in urothelial carcinoma of the bladder, and our previous work also revealed that low preoperative neutrophil to lymphocyte ratio was independently associated with worse survival outcomes . In addition, low serum cholesterol levels was also associated with poor survival in colorectal cancer and renal cell carcinoma, but the specific mechanism remained to be elucidated. In all, CONUT, a combination of these three indictors above, is more powerful and can be applicated in current risk stratifications of UTUC.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study of patients who underwent surgery for renal cell carcinoma, preoperative serum cholesterol was implicated as an independent factor for prognosis. Lower cholesterol levels were found to be associated with advanced disease and worse survival, which may be due to cholesterol's increased storage in tumour cells and role in new membrane biosynthesis [23]. For Pfam, 5 and 9 protein families were found based on duplication and total copy number burden, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As the terminology “clear cell” indicates, the clear cell type of RCC accumulates significant amounts of cholesterol ester and glycogen in the cytosol [20]. Furthermore, several genes involved in lipid metabolism were previously reported to be related with clear cell type RCC progression [21].…”
Section: Discussionmentioning
confidence: 99%